2017
DOI: 10.1007/s40843-017-9063-6
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of open-cellular (porous) titanium alloy implants: osseointegration, vascularization and preliminary human trials

Abstract: In this study we describe the fabrication of a variety of open-cellular titanium alloy (Ti-6Al-4V) implants, both reticular mesh and foam structures, using electron beam melting (EBM). These structures allow for the elimination of stress shielding by adjusting the porosity (or density) to produce an elastic modulus (or stiffness) to match that of both soft (trabecular) and hard (cortical) bone, as well as allowing for bone cell ingrowth, increased cell density, and all-matrix interactions; the latter involving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 29 publications
0
33
0
Order By: Relevance
“…This demonstrated their potential for clinical application in comparison to PEEK [160]. After three months, post-implantation, micro CT (computer generated) imaging and histological staining showed the growth of neighboring bone tissue into porous Ti mesh, partially fusing the two vertebral bodies.…”
Section: In Vivo Studies and Clinical Trials Of Ebm Fabricated 3d Scamentioning
confidence: 84%
See 3 more Smart Citations
“…This demonstrated their potential for clinical application in comparison to PEEK [160]. After three months, post-implantation, micro CT (computer generated) imaging and histological staining showed the growth of neighboring bone tissue into porous Ti mesh, partially fusing the two vertebral bodies.…”
Section: In Vivo Studies and Clinical Trials Of Ebm Fabricated 3d Scamentioning
confidence: 84%
“…The bone tissue bonded closely with Ti mesh/cage, with majority of bone tissue around the struts in the interior and peripheral regions of the mesh (Fig. 9) [160]. A comparative study showed that the culture of human osteoblast-like cells on Ti-6Al-4V led to enhanced osteogenic differentiation in comparison to PEEK implant [167].…”
Section: In Vivo Studies and Clinical Trials Of Ebm Fabricated 3d Scamentioning
confidence: 95%
See 2 more Smart Citations
“…Although commercial pure titanium and Ti6Al-4V alloy are most used for biomedical applications, there are still two remaining problems to be solved [2,3]. One is the potential toxicity of alloying elements, such as V ions released from Ti-6Al-4V alloy.…”
Section: Introductionmentioning
confidence: 99%